2014
DOI: 10.1038/gim.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic effect on FMR1 carrier rate and AGG repeat interruptions among Ashkenazi women

Abstract: introductionFragile X syndrome (FXS; OMIM 300624) is the most common form of inherited mental impairment, with a prevalence of approximately 1/4,500 in males. The syndrome is characterized by moderate intellectual disability and behavioral abnormalities, including autistic-like behavior.1,2 The vast majority of FXS cases are caused by an expansion of CGG nucleic-base repeats in the Fragile X mental retardation gene (FMR1). Normal individuals usually have ~30 CGG repeats. An expansion to greater than 200 repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…A subset of the sample in our study is AJ. A recent study that evaluated 4,344 AJ and 4,985 non-AJ subjects reported a higher rate of premutations in the 55–59 repeat range (1:114 vs. 1:277) among the AJ women and concluded that AJ women have a high fragile X syndrome carrier rate and mostly low-range premutations [11]. In the AJ ET cases (including AJ ET females) and non-AJ ET cases that we analyzed in the current study we did not observe a higher proportion of premutations.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of the sample in our study is AJ. A recent study that evaluated 4,344 AJ and 4,985 non-AJ subjects reported a higher rate of premutations in the 55–59 repeat range (1:114 vs. 1:277) among the AJ women and concluded that AJ women have a high fragile X syndrome carrier rate and mostly low-range premutations [11]. In the AJ ET cases (including AJ ET females) and non-AJ ET cases that we analyzed in the current study we did not observe a higher proportion of premutations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there was insufficient funding to measure potential variation in the repeat structure within different race/ethnic groups, such as AGG interruptions, which would have been informative given the reported differences in AGG interruption patterns across 9 countries 35 and ethnicity. 11 The primary strength of this study is the ability to examine race-ethnic genetic differences within a single study due to the SWAN recruitment design. Additional study strengths include the known normal fertility history, the large cohort size, and the community-based sample (so that founder effects are not influencing the distributions).…”
Section: Discussionmentioning
confidence: 99%
“…12 Five of these articles reported separate results for females. [9][10][11]16,19 Nine of the 10 studies that included females reported the total allelic distribution, 9,11,[15][16][17][18][19][20][21] and none of those publications reported the FMR1 distribution of the higher allele separate from the lower allele. The recent article by Voorhuis et al 10 did report separate results for the higher and lower alleles among females from the general population, but their population included women with early menopause at ages 40 to 45 and infertility.…”
Section: Existing Population Data In the Range Ofmentioning
confidence: 99%
“…One of the important limitations of this study concerns the lack of analyses stratified by other related susceptible factors, such as race and ethnicity have not been conducted in the present study because insufficient data were available from the primary studies. Race/ethnic differences in the FMR1 CGG repeat distribution have been reported [37][38][39]. However, the results from individual studies were inconsistent.…”
Section: Discussionmentioning
confidence: 99%